Measured Language: Quantitative Studies of Acquisition, Assessment, and Variation - Jeffrey Connor-Linton, Luke Wander Amoroso (Georgetown University Press, 2014)
The Georgetown University Round Tables on Languages and Linguistics (GURT) and their attendant published volumes of selected papers have historically offered seminal contributions to the field of linguistics; papers from GURT volumes are frequently referenced in journal articles and are often required reading for graduate linguistics courses. The continued relevance of GURT publications stems from their coverage over the years of the many different areas of inquiry that constitute linguistics. With topics ranging from language teaching and education to discourse analysis, technology, and language-specific research, GURT conferences draw linguists from around the world. The 2012 Round Table focused on the ways in which various aspects of language can be quantified, and how measurement informs and advances our understanding of language. The metaphors and operationalizations of quantification serve as an important lingua franca for much linguistic research, allowing methods and constructs to be translated from one area of linguistic investigation to another. A primary goal of the conference and this volume was to provide a forum for exploring relations among constructs developed from seemingly disparate theoretical and methodological perspectives. While many previous GURT volumes have focused on a single method of linguistic analysis or considered a particular theoretical problem from many different perspectives, we took a different approach. We called for studies that employed quantitative methods of measuring language acquisition, assessment, and variation in the belief that quantification for one particular purpose would prove useful to researchers investigating other linguistic questions. We believe that researchers in these areas of linguistics have much to learn from each other, both conceptually and methodologically, so conference contributors were asked to share the relevance of their perspectives and findings to other areas of linguistic inquiry. For this volume we have selected papers that illustrate forms of measurement and quantitative analysis that are current in diverse areas of linguistic research, from language assessment to language change, from generative linguistics to psycholinguistic experimentalism, and from longitudinal studies to classroom research. The range and clarity of the research collected here ensures that even linguists who would not traditionally use quantitative methods will find this volume useful.